Leverage, Fixed Assets and Board Characteristics on Financial Performance of Non-Cyclicals Companies - Muhammad Rizky; Yusrina Almas Sajida; Henny Setyo Lestari; Farah Margaretha (Universitas Negeri Semarang, 2024)
This study aims to analyze the impact of noncyclical company characteristics, board of director composition, and leverage on financial performance in Indonesia. The researcher uses quantitative research methodology to collect and analyze data. To investigate the impact of significant factors on each other, this study uses multiple linear regression analysis as its data analysis approach. The 66 sampled organizations all have data collected from their annual reports between 2019 and 2023. The result of the analysis shows that ROA and ROE impacted by the debt ratio. Tangible assets have an impact on ROE but not impact on ROA. Board size positively affects ROA but not affect on ROE. Board independence influences ROA but has no effect on ROE. ROA and ROE are impacted by firm size.